Aquablation: a novel and minimally invasive surgery for benign prostate enlargement. Issue 6 (June 2018) - Taktak, Samih; Jones, Patrick; Haq, Ahsanul; Rai, Bhavan Prasad; Somani, Bhaskar K.
Aquablation is a minimally invasive surgical technology for benign prostate enlargement, which uses high-pressure saline to remove parenchymal tissue through a heat-free mechanism of hydrodissection. Early results show this to be a promising surgical strategy with a strong morbidity profile and reduced resection time. This review serves to provide an overview of the technique and evaluate its safety and efficacy.